3y - 3 = 2y + 5 3y - 2y = 5 + 3 y = 8
x + 3
9x + 5 = 4x + 3 Subtract 4x from both sides: 5x + 5 = 3 Subtract 5 from both sides: 5x = - 2 Divide both sides by 5: x = -2/5 or -0.4
13
-3
2a + 4b - 52a + 4b - 52a + 4b - 52a + 4b - 5
If 3a+5=5a+3, then: 3a+5 - 3a = 5a+3 - 3a 5=2a+3 5 - 3=2a+3 - 3 2=2a a=1
9a +8 -2a -3 -5a = 2a +5
(6a3 - 19a2 + 15a)/(2a - 3) = a(6a2 - 19a + 15)/(2a - 3) = a(2a - 3)(3a -5)/(2a -3) = a(3a - 5)
(a - 5)(a + 3) = a2 - 2a - 15
a+b+2+3=5+a+b
its a quadratic equation. (4b-5) (4b-5)
Well if it is worded right then 4xb-1+(-4)+4b=4b-1-4+4b=4b+4b-1-4=8b-5
4b plus 7b plus 5 will equal 11b plus 5. When you have two variables that are the same you can add the two numbers with the variables remaining the same.
-2b+8-4b = -5-11b+7 -2b-4b+11b = -5+7-8 5b = -6 b = -6/5
5a - 5 = 7 + 2a ( subtract 2a from both sides) 3a - 5 = 7 (add 5 to both sides) 3a = 12 ( divide both sides by 3) a = 4
= 3 X 2 = 6 = a X a = a2 (a square) = 6a2 + 5 Answer